1999
DOI: 10.1016/s0022-5347(05)68247-x
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Atropine-Resistant Contractile Responses in Human Detrusor Smooth Muscle, From Stable, Unstable and Obstructed Bladders

Abstract: It is concluded that purinergic, atropine-resistant contractions are present in some types of dysfunctional bladder, and these are not caused by a differential sensitivity of the muscle to ATP and cholinergic agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(131 citation statements)
references
References 25 publications
5
121
1
4
Order By: Relevance
“…Furthermore, since there were no differences in the effects of carbachol or ATP, then the observed increase of the contractile response to EFS must be due to presynaptic mechanisms rather than postsynaptic effects. This would fit with evidence that in neurogenic bladder and hypertrophic unstable bladder syndromes, TTX-sensitive but atropine resistant, purinergic contractions are increased [16, 2931]. In neurogenic bladder, it was shown that there was a marked increase in the purinergic contribution to parasympathetic control of bladder contractility [15].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, since there were no differences in the effects of carbachol or ATP, then the observed increase of the contractile response to EFS must be due to presynaptic mechanisms rather than postsynaptic effects. This would fit with evidence that in neurogenic bladder and hypertrophic unstable bladder syndromes, TTX-sensitive but atropine resistant, purinergic contractions are increased [16, 2931]. In neurogenic bladder, it was shown that there was a marked increase in the purinergic contribution to parasympathetic control of bladder contractility [15].…”
Section: Discussionsupporting
confidence: 69%
“…For example, bladder preparations from interstitial cystitis patients showed increased sensitivity of contractions to purine receptor desensitization with α,β-methylene ATP (Palea et al, 1993). Likewise, bladder detrusor preparations from obstructed bladders demonstrated significant atropine-resistant contractions that were abolished by TTX or by α,β-methylene ATP (Bayliss et al, 1999). P2X1 receptors are believed to be the predominant receptor mediating purinergic contractions in human bladder, and their expression appears to be increased in obstructed bladders compared with control bladders (O’Reilly et al, 2001; O’Reilly et al, 2002).…”
Section: Evidence For Release Of Purine Neurotransmittersmentioning
confidence: 99%
“…Bladder strips were also used to investigate myogenic and neuronal factors that modulate smooth muscle tone with the aim of discovering ion channels and/or receptors and/or intracellular pathways that could be targeted to induce either relaxation or contraction of the smooth muscle 3,1013 . Other studies have focused on the nature of neurotransmission, including transmitters and receptors involved and changes induced by pathology 14,15 . In addition, the method has been used for comparisons between tissues from different species 1618 , between organs 1921 , and evaluation of drug structure-activity relationships 2224 .…”
Section: Introductionmentioning
confidence: 99%